Oculopharyngodistal myopathy--a possible association with cardiomyopathy. - Thevathasan, W; Squier, W; MacIver, D; Hilton, D; Fathers, E; Hilton-Jones, D (2011)
Oculopharyngodistal myopathy is an uncommon myopathy characterised clinically by cranial and distal limb muscle weakness. Here we describe two siblings with autosomal dominant oculopharyngodistal myopathy apparently associated with dilated cardiomyopathy, which in one case progressed to ventricular hypertrabeculation/non-compaction. Electrocardiographic screening was normal and the cardiomyopathy was detected only with echocardiography. Our findings suggest that patients with oculopharyngodistal myopathy should be screened for cardiomyopathy (with both electrocardiography and echocardiography).